2017
DOI: 10.1051/shsconf/20173300078
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Pattern of Internal Communication in Total Quality Management Implementation in Manufacturing Companies

Abstract: Communication is an important aspect of organizational dynamic process and it is irrefutable one of the critical success factors of the Total Quality Management (TQM) implementation. Although there are increasing awareness concerning the importance of internal organizational communication, knowledge appears to have rarely translated into practice or there is lack of guidance to effectively practicing it. Therefore, a study was proposed to investigate the pattern of internal communication practice in TQM implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…There is a positive correlation between communication from top management to subordinates and the work environment [4] . On the contrary, [9] investigated the model of communication practice in Quality implementation. The research suggested prevalence of some patterns of communication practiced by the management during conveyance and dissemination of Quality messages, but highlighted absence of any specific guidelines.…”
Section: B Communication and Total Quality Managementmentioning
confidence: 99%
“…There is a positive correlation between communication from top management to subordinates and the work environment [4] . On the contrary, [9] investigated the model of communication practice in Quality implementation. The research suggested prevalence of some patterns of communication practiced by the management during conveyance and dissemination of Quality messages, but highlighted absence of any specific guidelines.…”
Section: B Communication and Total Quality Managementmentioning
confidence: 99%